Hermeneutic Dimension of Lexical-Syntactic Word Formation (in Ukrainian Language and Literature) - Andrishko, Oleh; Popovskyi, Anatoliy (2022)
The article considers lexical and syntactic word formation based on works of Ukrainian literature. Hermeneutics is closely related to philology, but most often examines the text from the point of view of literary criticism. The linguistic aspect, namely the study of occasionalisms, is much less studied. Attention to Ukrainian culture is growing, and in this context it can be an interesting source of hermeneutic research. This article examines the most interesting examples of occasionalisms, which by their function and non-standard structure are divided into two types – a priori and a posteriori. The difference between coalescences (words formed in a lexical-syntactic way) and similar words and phenomena has also been clarified. Most of these words are related to holophrases, but in Ukrainian literature there are examples that we call a posteriori coalescences, they are formed according to individual authorial models and have almost no analogues in the texts of other writers. We hope that this study will be an important step in the study of Ukrainian language and literature in the world and will draw attention to Ukrainian culture – a culture with millennial traditions.
Keywords: lexical-syntactic word formation; coalescence; Ukrainian language; Ukrainian literature; a priori and a posteriori occasionalisms